EFL STUDENTS’ PERCEIVED VALUE IN VIDEO PROJECTS - Putri, Dede Adelia; Sofyan, Ryan Rayhana; Sally, Fauzan Hari Sudding (JTechLP: Journal of Technology in Language Pedagogy, 2026)
This study explores how students learning English as a foreign language (EFL) view the value of using video projects in their learning process. Using the framework of the Situated Expectancy-Value Theory (SEVT), the research focuses on how students feel about the usefulness, importance, and enjoyment of creating videos during their English course. A total of 149 students from the Intermediate English Grammar class at Universitas Negeri Makassar completed a questionnaire. The results showed that most students found video projects highly valuable. Many believed these tasks helped improve their English skills, creativity, and preparation for future careers. This suggests that video projects can support both learning and student motivation in EFL classes.